Bipartite multi-tracking in MASs with intermittent communication - Huang, Da; Fan, Xiaolin; Hu, Cheng; Jiang, Haijun (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, a novel cluster consensus problem related with the bipartition of the graph of multi-agent systems (MASs) is studied. To track the virtual leaders and reach the expected consensus, a new type of pinning consensus protocol with aperiodic intermittent effects is designed according to the graph structure, and a new kind of aperiodic intermittent communication is defined. Moreover, the protocol is applied to construct networked systems with intermittent communications. Lyapunov functional is applied to get sufficient conditions for solving the multi-tracking problem under a dual subsystem framework. Finally, some numerical simulations are given to illustrate the effectiveness of the theoretical results.